Curating, interpretation and museums : when attitude becomes form - Lahav, Sylvia (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Following a period of ideological and practical change in museums, this book outlines new attitudes in curating and display, education and learning, text and interpretation, access, inclusion, participation, space, and the sustainability of the encyclopaedic collection. Focused on the contemporary period, the author questions the extent to which the museum visitor has become reliant on interpretative text and examines the development of new museum spaces where visitor interaction and engagement is welcomed. Changes of attitude have transformed our museums into modern spaces that reflect current needs and modern expectations and yet our permanent collections remain relatively unchanged, sometimes an uncomfortable reminder of a time when values, ethics and attitudes were very different. The author will discuss these conflicts of ideology. Written by a researcher with expertise in museum practice, this shortform book offers a new approach that will be valuable reading for students and scholars of cultural management and policy, as well as providing insights for reflective museum practitioners"--
Collecting, exhibiting and curating -- Interpretation and text -- Space and place -- Whose knowledge, whose history, whose culture, whose words and whose legacy? -- Looking back...final thoughts.
OCLC-licensed vendor bibliographic record.
Keywords: Museums -- Curatorship -- Social aspects; BUSINESS & ECONOMICS / Museum Administration & Museology; BUSINESS & ECONOMICS / Nonprofit Organizations & Charities; ART / Business Aspects